Penggunaan Teknik Slow Stroke Back Massage Terhadap Perubahan Kualitas Tidur Pada Pasien Stroke Iskemik - Izatul Murni; Yenny Safitri; Indrawati Indrawati (LPPI Yayasan Almahmudi Bin Dahlan, 2025)
Stroke is one of the cerebrovascular diseases that is a serious problem worldwide, causing paralysis and a high mortality rate. This disease occurs due to a disruption in brain function related to the blood vessels that supply blood flow to the brain, causing blockages and ruptures. The purpose of this scientific work is to obtain an overview of nursing care with the provision of Slow Stroke Back Massage therapy. This research was conducted in the Krisan Room of Arifin Achmad Regional General Hospital in Riau Province. The type of research is descriptive qualitative research. This research was conducted on June 8-10, 2025, with a sample of 1 respondent. The results of this study indicate that after receiving Slow Stroke Back Massage therapy once a day for three consecutive days, there was an improvement in sleep quality. It is hoped that ischemic stroke patients can apply Slow Stroke Back Massage therapy if they experience sleep issues.